Manajemen Bank Sentral: Fungsi, Tugas Dan Peran Pentingnya Dalam Stabilitas Ekonomi - Faikoh Faikoh; Afidatur Rizqiyah; Rini Puji Astuti (PT. Padang Tekno Corp, 2025)
Central banks play a key role in maintaining macroeconomic stability through monetary policy, financial system supervision, and payment system control. This article comprehensively discusses the functions, duties, and strategic roles of central banks in creating national economic resilience in the midst of global dynamics. Using a qualitative approach, this article also reviews the various modern challenges facing central banks, including the influence of globalization, developments in financial technology, climate change, and dependence on global debt. The findings show that the effectiveness of the central bank's role is highly dependent on policy adaptability, cross-agency coordination, and transparent public communication. Therefore, responsive and innovative central bank management is an important foundation in ensuring long-term economic stability.